Anti-toxicity test of Peperomia pellucida steeping on liver function in diabetic-induced rat - Saryono Saryono; Hernayanti Hernayanti; Atikah Proverawati (Molekul, 2020)
Liver is important for both defense mechanism and protein synthesis in the human body. This study examined the anti-toxicity of Peperomia pellucida on liver function of diabetic-induced rats. It was an experimental study using pre- and post-test control group design. Rats were categorized into five groups, i.e., groups of healthy control (A), negative control (B), and treatment (C-E) with dosages of 150, 300, and 600 mg/kg of P. pellucida, respectively. Each group comprises of 5 rats. The TNF-a, IL-12, and GSH were measured before and after a 14 days administration of P. pellucida. The data were analyzed by using one-way ANOVA test followed by Duncan's post hoc test with a significance level of 5%. The result showed that P. pellucida steeping can improve liver cell damage, which was shown from the parameters of liver function, inflammation, and antioxidants. The mean of TNF-a and IL-12 levels decreased while the total protein, albumin, and GSH levels increased significantly after administration of P. pellucida steeping. Our study concluded that P. pellucida steeping might reduce TNF-a and IL-12 levels, and increased GSH level in diabetic-induced rat. A 300 mg/kg was the most effective dosage to reduce IL-12 and increase GSH.